A comparative study of impact on cognitive function between diabetic and non-diabetic patients in a tertiary care hospital - Patel, Dharnaben A.; Patel, Dhruv J.; Kantharia, N. D. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Diabetes Mellitus is a chronic metabolic disorder characterized by hyperglycemia, polyuria, hyperlipidemia etc, resulting from defects in insulin secretion, insulin action or both. It affects various organs of the body including the brain. Cognitive function is the thinking process of the brain. In any chronic disease evaluation of cognitive function is justified as it may affect various common day to day activities. Methods: It is a prospective, observational and non-interventional study. Thirty diabetic patients who were recently started on insulin i.e. within 7 days were enrolled in the study based on inclusion and exclusion criteria. Thirty non diabetic healthy individuals served as a control. Cognitive function was accessed by Adenbrooke’s Cognitive Examination (ACE III) at the time of enrollment. Results: The results were analysed using paired t-test. Attention, Memory and Visiospatial ability was significantly reduced in diabetic patients compared to control. Verbal fluency and language was also reduced but the change was not significant. Total ACE III score was significantly reduced in diabetic patients compared to control. Conclusions: Cognitive function is significantly reduced in Diabetic patients recently started on insulin. Hyperglycemia could be the possible reason of cognitive decline. Proper understanding of the natural history of Diabetes and the pathogenesis of cognitive decline as well as control of Diabetes can help to prevent development of cognitive dysfunction.